Health risk assessment due to exposure of arsenic contamination in drinking water of district Shiekhupura, Punjab, Pakistan. Issue 1 (2nd January 2020) - Ehsan, Nusrat; Shan, Ali; Riaz, Shoaib; uz Zaman, Qamar; Javied, Sabiha; Jabeen, Mahwish
Abstract: The present study was conducted to assess the magnitude and health impacts of As in drinking water. Drinking water samples (n = 60) were collected from twenty different sites of Shiekhupura District (Pakistan). Health risk assessment through average daily dose (ADD), hazard indices (HI), hazard quotient (HQ), carcinogenic risk (CR), and cancer indices (CI) for dermal and oral exposure were determined. Results revealed that As concentration ranged from 2 to 900 µg L −1 in water samples, which was significantly greater than the safe limit of As (10 µg L −1 ) in water. Health risk assessment of As showed that ADD (1.07E−02–9.85E−04), HQ (1.06E+01–9.85E+00), and CR (1.60E−02–9.85E−04) for oral exposure and ADD (1.03E−05–9.69E−06), HQ (1.19E−02–7.96E−03), and CR (1.11E−05–8.98E−05) for dermal exposure which were exceeded the toxic risk index value. Comparison of the two exposure pathways indicated that the oral exposure is much higher risk than the dermal contact. Both values of HI and CI were greater than WHO limit. It is concluded that residents of study area are at higher risk of As induced diseases and carcinogenicity.